Integrating islands of knowledge for greater synergy and efficiency in crop research. (February 2017) - Borrell, Andrew; Reynolds, Matthew
Abstract: A transnational approach to plant science is required to address global challenges such as food security and climate change. Action from the plant, crop and agricultural science communities will be required to meet these challenges. Islands of knowledge (e.g. crop, discipline, scale, environment, organization) need to be better integrated. Mapping is needed to identify gaps and make connections between these islands. Translational research, spanning from the molecular to farm scale, should be the focus. We need more `integrators' to manage complex global projects and integration should be recognized as an important skill in itself. We need to advocate teamwork over individuality ‐ and reward teams. Impact should be taken much more seriously as an outcome and we need to better understand impact pathways. Focusing on key game‐changers will more likely lead to impact rather than attempting to do everything. Abstract : Building bridges between islands of knowledge should enhance the impact of global research addressing food security (background image fromwww.world.time.com ).